Circulating microRNAs Associated With Reversible Cerebral Vasoconstriction Syndrome. Issue 3 (30th December 2020) - Chen, Shih‐Pin; Chang, Yi‐An; Chou, Chih‐Hung; Juan, Chi‐Chang; Lee, Hsin‐Chen; Chen, Luen‐Kui; Wu, Pei‐Chun; Wang, Yen‐Feng; Fuh, Jong‐Ling; Lirng, Jiing‐Feng; Ducros, Anne; Huang, Hsien‐Da; et al.
Abstract : Objective: The purpose of this study was to investigate the significance of circulating micro RNAs (miRNAs) in the pathogenesis of reversible cerebral vasoconstriction syndrome (RCVS). Methods: We prospectively recruited 3 independent cohorts of patients with RCVS and age‐matched and sex‐matched controls in a single medical center. Next‐generation small RNA sequencing followed by quantitative polymerase chain reaction (PCR) was used to identify and validate differentially expressed miRNAs, which was cross‐validated in migraine patients in ictal stage or interictal stage. Computational analysis was used to predict the target genes of miRNAs, followed by in vitro functional analysis. Results: We identified a panel of miRNAs including miR‐130a‐3p, miR‐130b‐3p, let‐7a‐5p, let‐7b‐5p, and let‐7f‐5p that well differentiated patients with RCVS from controls (area under the receiver operating characteristics curve [AUC] was 0.906, 0.890, and 0.867 in the 3 cohorts, respectively). The abundance of let‐7a‐5p, let‐7b‐5p, and let‐7f‐5p, but not miR‐130a‐3p nor miR‐130b‐3p, was significantly higher in patients with ictal migraine compared with that of controls and patients with interictal migraine. Target prediction and pathway enrichment analysis suggested that the transforming growth factor‐β signaling pathway and endothelin‐1 responsible for vasomotor control might link these miRNAs to RCVS pathogenesis, which was confirmed in vitro by transfecting miRNAs mimics or incubating the patients' cerebrospinal fluid (CSF) in 3 different vascular endothelial cells. Moreover, miR‐130a‐3p was associated with imaging‐proven disruption of the blood‐brain barrier (BBB) in patients with RCVS and its overexpression led to reduced transendothelial electrical resistance (ie, increased permeability) in in vitro human BBB model. Interpretation: We identified the circulating miRNA signatures associated with RCVS, which may be functionally linked to its headache, BBB integrity, and vasomotor function. ANN NEUROL 2021;89:459–473